Question
upstudy study bank question image url

Solve For \( x \) 1. \( 2 \sqrt{x+2}=x-1 \)

Ask by Haynes Mitchell. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( x=7 \)

Solution

Solve the equation \( 2\sqrt{x+2}=x-1 \). Solve the equation by following steps: - step0: Solve for \(x\): \(2\sqrt{x+2}=x-1\) - step1: Find the domain: \(2\sqrt{x+2}=x-1,x\geq -2\) - step2: Rewrite the expression: \(\sqrt{x+2}=\frac{x-1}{2}\) - step3: Evaluate: \(\sqrt{x+2}=\frac{x-1}{2},\frac{x-1}{2}\geq 0\) - step4: Evaluate: \(\sqrt{x+2}=\frac{x-1}{2},x\geq 1\) - step5: Solve the equation: \(\begin{align}&x=7\\&x=-1\end{align},x\geq 1\) - step6: Find the intersection: \(x=7\) - step7: Check if the solution is in the defined range: \(x=7,x\geq -2\) - step8: Find the intersection: \(x=7\) - step9: Check the solution: \(x=7\) The solution to the equation \(2\sqrt{x+2}=x-1\) is \(x=7\).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

To solve the equation \( 2 \sqrt{x+2} = x - 1 \), first isolate the square root by dividing both sides by 2: \[ \sqrt{x+2} = \frac{x-1}{2} \] Next, square both sides to eliminate the square root: \[ x + 2 = \left(\frac{x-1}{2}\right)^2 \] Expanding the right side gives: \[ x + 2 = \frac{(x-1)^2}{4} \] Now, multiply both sides by 4 to eliminate the fraction: \[ 4(x + 2) = (x-1)^2 \] This expands to: \[ 4x + 8 = x^2 - 2x + 1 \] Rearranging the equation brings all terms to one side: \[ 0 = x^2 - 2x + 1 - 4x - 8 \] Combining like terms results in: \[ 0 = x^2 - 6x - 7 \] Now, factor the quadratic equation: \[ 0 = (x - 7)(x + 1) \] Setting each factor to zero gives the solutions: \[ x - 7 = 0 \quad \Rightarrow \quad x = 7 \] \[ x + 1 = 0 \quad \Rightarrow \quad x = -1 \] Finally, we need to check both solutions in the original equation. For \(x = 7\): \[ 2 \sqrt{7 + 2} = 2 \sqrt{9} = 2 \cdot 3 = 6 \] \[ 7 - 1 = 6 \quad \Rightarrow \quad \text{Valid solution!} \] For \(x = -1\): \[ 2 \sqrt{-1 + 2} = 2 \sqrt{1} = 2 \] \[ -1 - 1 = -2 \quad \Rightarrow \quad \text{Invalid solution!} \] Thus, the only solution is: \[ \boxed{7} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy